2016
DOI: 10.1016/j.ajpath.2015.12.022
|View full text |Cite
|
Sign up to set email alerts
|

miR-133b Regulation of Connective Tissue Growth Factor

Abstract: miRNAs are involved in liver regeneration, and their expression is dysregulated in hepatocellular carcinoma (HCC). Connective tissue growth factor (CTGF), a direct target of miR-133b, is crucial in the ductular reaction (DR)/oval cell (OC) response for generating new hepatocyte lineages during liver injury in the context of hepatotoxin-inhibited hepatocyte proliferation. Herein, we investigate whether miR-133b regulation of CTGF influences HCC cell proliferation and migration, and DR/OC response. We analyzed m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 50 publications
0
17
0
1
Order By: Relevance
“…Studies have shown that CTGF can activate multiple signalling pathways, including ERK, p38, JNK, ROS, ASK1 and NF-κB, and promote the migration and proliferation of human Tenon's capsule fibroblasts, hepatic stellate cells (HSCs), hepatoma carcinoma cells, cardiomyocytes and glioma cells 17 - 22 . Our former research findings showed that CTGF is under the regulation of the TGF-β/Smad signalling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that CTGF can activate multiple signalling pathways, including ERK, p38, JNK, ROS, ASK1 and NF-κB, and promote the migration and proliferation of human Tenon's capsule fibroblasts, hepatic stellate cells (HSCs), hepatoma carcinoma cells, cardiomyocytes and glioma cells 17 - 22 . Our former research findings showed that CTGF is under the regulation of the TGF-β/Smad signalling pathway.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, CTGF and VEGFA have not been previously implicated in fibroblast activation. Although CTGF level is regulated via miRNA mechanisms in the contexts of liver pathology (22), diabetic nephropathy (23), and hyperplastic scar formation (24), these studies focused exclusively on autocrine effects, whereas the paracrine effect of tumor-secreted CTGF on other cell types in the tumor vicinity has not been studied. Similarly, VEGFA has a well-established role in tumor vascularization, but its function has not been linked to fibroblast activation, even though the duration of fibroblast activation appears to coincide well with the induction of new blood vessels prior to metastatic spread (17).…”
Section: Discussionmentioning
confidence: 99%
“…Two members of the BCL-2 family of pro-survival molecules (MCL-1 and BCL2L2 (BCLw)) as predicted targets of miR-133b have been identified in lung cancer, osteosarcoma, bladder cancer and gastric cancer (Mcl-1 and Bcl-xL), in which over-expression of miR-133b can induce apoptosis though theses apoptosis regulator in tumor cells [ 27 30 ]. Yet expect all the apoptotic pathways, miR-133b can regulate genes closely related to proliferation, such as fibroblast growth factor receptor 1 (FGFR1), and Sp1 and its downstream proteins Cyclin D1 in gastric cancer [ 31 , 32 ], TATA-box binding protein like 1(TBPL1) in colorectal cancer [ 33 ], the human ether-a-go-go-related gene potassium channel (hERG, Kv11.1, KCNH2) in glioma [ 34 ]and connective tissue growth factor(CTGF) in hepatocellular carcinoma (HCC) [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…(Figure 3B, 3C ), Table 1 . Fascin actin-bundling protein 1(FSCN1), which plays a critical role in cell migration, motility, adhesion and cellular interactionsin, in esophageal squamous cell carcinoma (ESCC) [ 61 ], gastrointestinal stromal tumor(GIST) [ 62 ] and gastric cancer [ 63 ], C-X-C motif chemokine receptor 4(CXCR4) and in colorectal cancer [ 64 ], IGF1R, MET, phospho-Akt and FAK in osteosarcoma [ 28 ], Gli1 in gastric cancer(GC) [ 65 ], Sp1 and its downstream proteins MMP-9 in GC [ 32 ], CTGF in HCC [ 35 ].…”
Section: Introductionmentioning
confidence: 99%